Fabrication of disk-shaped, deuterated resorcinol/formaldehyde foam target for laser–plasma experiments - Kaneyasu Y; Nagai K; Cadatal-Raduban M; Golovin D; Shokita S; Yogo A; Jitsuno T; Norimatsu T; Yamanoi K (Cambridge University Press in association with Chinese Laser Press, 2021)
Resorcinol/formaldehyde (RF) foam resin is an attractive material as a low-density target in high-power laser–plasma experiments because of its fine network structure, transparency in the visible region, and low-Z element (hydrogen, carbon, and oxygen) composition. In this study, we developed disk-shaped RF foam and deuterated RF foam targets with 40–200 µm thickness and approximately 100 mg/cm3 density having a network structure from 100 nm to a few micrometers cell size. By deuteration, the polymerization rate was drastically slowed down owing to kinetic isotope effects. These targets were used in high-power laser experiments where a megaelectronvolt proton beam was successfully generated.
Keywords: deuterated material; low-density material; resorcinol; formaldehyde foam